LOCALIZED OXIDE TRAPPED CHARGE’S EFFECT ON THE CAPACITANCE BETWEEN GATE-SOURCE IN FINFET DEVICES - Foziljonov Mirzabaxrom Baxtiyorjon o’g’li; Raxmonkulova Nargizaxon Baxromjon qizi (World Scientific Research Journal, 2025)
Abstract. This study examines the effect of localized oxide trapped charge on the capacitance of the gate-to-source (drain) connection in silicon-on-insulator (SOI) based FinFET devices. The capacitance-voltage characteristics of the gate-source capacitance are analyzed using a small AC signal technique. The gate-source (gate-drain) capacitance is evaluated at various positions along the channel where the localized oxide trapped charge is present. Additionally, the distribution of charge carriers along the channel at different locations of the localized oxide trapped charge is taken into account. The results demonstrate a consistent increase in the gate-source capacitance as the distance between the source-channel boundary and the center of the localized charge increases.